Effects of calcium and ferric ions on struvite precipitation: A new assessment based on quantitative X-ray diffraction analysis. (15th May 2016) - Yan, Hanlu; Shih, Kaimin
Abstract: The precipitation of struvite (MgNH4 PO4 ·6H2 O) from waste streams has attracted considerable attention due to its potential for recovering phosphorus for fertilization. As struvite is primarily acquired by means of precipitation and crystallization from aqueous solutions, it is important to evaluate the roles of common metal ions, particularly those that are commonly found in wastewater, in the struvite crystallization process. This study was performed to quantitatively evaluate the effects of calcium and ferric ions on struvite crystallization using the Rietveld refinement method, which is based on the analysis of X-ray diffraction data. The results indicate that both calcium and ferric ions significantly inhibit the formation of struvite crystals, and the effects vary under different pH conditions. There was a negative linear correlation between the struvite weight content in the precipitates and the Ca/Mg molar ratio in the initial solution. However, ferric ions were confirmed to be a more efficient inhibitor of struvite crystallization. Ca 2+ and Fe 3+ further modified the needle-like struvite into irregular shapes. An unambiguous and quantitative understanding of the effects of foreign ions on struvite crystallization will help to reliably improve the quality of struvite products recovered from wastewater and the control of struvite deposits in water and sludge piping systems. Graphical abstract: Highlights: Quantitative-XRD method is employed to analyze struvite contents in precipitates. Struvite content is with a negative linear correlation to Ca/Mg molar ratio. PH ≥ 10.0 adversely affects struvite and hydroxyapatite crystallization. Fe 3+ is a more effective inhibitor for struvite crystallization compared to Ca 2+ .